The first group 4 metal bis(imido) and tris(imido) complexes - Schwarz, A; Nielson, A; Kaltsoyannis, N; Mountford, P (2012)
We report a combined experimental and computational study of the first bis(imido) and tris(imido) complexes of a group 4 metal. Reaction of [Ti(NAr)(NHAr) 2(py) 2] (1, Ar = 2,6-C 6H 3iPr 2) with 3 equivs. of MeLi gave the lithium-stabilised tris(imide) [TiMe(NAr) 3{Li(py)} 3] (2). Reaction of 1 with 2 equivs. of MeLi in the presence of ArNH 2 gave the corresponding bis(imide) [Ti(NAr) 2(NHAr) 2{Li(py)} 2] (3). All three compounds 1, 2 and 3 have substantial Ti-N imide multiple bond character. Orbital and Mayer bond order analysis show that the formal bond orders are best viewed as ca. 3, 2.5 and 2, respectively, with a further attenuating effect on the multiple bonding by the [Li(py)] + ion coordination. Compounds 2 and 3 are the first examples of any group 4 metal simultaneously containing two or three multiply-bonded ligands. © 2012 The Royal Society of Chemistry.